2004
DOI: 10.1210/jc.2004-0720
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Neuroendocrine Control of Reproductive Function Despite Severe Undernutrition

Abstract: Anorexia nervosa (AN) is characterized by low weight and self-imposed caloric restriction and leads to severe bone loss. Although amenorrhea due to acquired GnRH deficiency is nearly universal in AN, a subset of patients maintains menses despite low weight. The mechanisms underlying continued GnRH secretion despite low weight in these patients and the impact of gonadal hormone secretion on bone mineral density (BMD) in such eumenorrheic, low-weight patients remain unknown. We hypothesized that 1) eumenorrheic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 29 publications
4
71
0
2
Order By: Relevance
“…In addition, current weight after correction for age and height was the best predictor of current bone mineral density, while menstrual status, reduced caloric intake, binge eating, vomiting, use of estrogen, laxatives, and nicotine did not significantly predict BMD. In contrast, the Miller et al 29 study described earlier found that bone mineral density was significantly lower at the posterior-anterior lumbar and lateral spine as was total body and radius BMD in the amenorrheic group compared with the menstruating group and these groups were of similar weights. These investigators did not find differences in bone density at the hip.…”
Section: Amenorrhea and Bone Healthmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, current weight after correction for age and height was the best predictor of current bone mineral density, while menstrual status, reduced caloric intake, binge eating, vomiting, use of estrogen, laxatives, and nicotine did not significantly predict BMD. In contrast, the Miller et al 29 study described earlier found that bone mineral density was significantly lower at the posterior-anterior lumbar and lateral spine as was total body and radius BMD in the amenorrheic group compared with the menstruating group and these groups were of similar weights. These investigators did not find differences in bone density at the hip.…”
Section: Amenorrhea and Bone Healthmentioning
confidence: 65%
“…A study by Miller et al 29 included a large sample of 74 women with DSM-IV AN and 42 women who met all DSM-IV criteria for AN except amenorrhea. The authors found that percent ideal body weight (IBW), BMI, duration of AN, age of menarche and hours per week of exercise were not significantly different between the groups.…”
Section: Clinical Features and Amenorrheamentioning
confidence: 99%
“…67,77,78 A direct comparison of 74 patients fulfilling all diagnostic criteria for AN with 42 eating disorderd eumenorrhoeic females who only fulfilled the first three DSM-IV criteria for AN, but who nevertheless had a similar BMI and severity of eating disorder symptomatology, revealed higher fat mass and per cent fat mass in the eumenorrhoeic in comparison to the amenorrhoeic females; as expected levels for oestradiol, insulin growth factor-1 (IGF-1) and leptin (3.770.3 vs 2.870.2 mg/l; P = 0.04) were lower in the amenorrhoeic patients. 79 In 17 adult AN patients who were not menstruating after 6-12 months of treatment during which mean BMI and mean leptin levels increased from 14.970.5 to 19.370.4 and 2.270.1 to 6.471.4 mg/l, respec-tively, 52 clomiphene treatment led to an on average five-and 50-fold increase in LH and oestradiol levels. Serum leptin levels were not different in those nine patients who initiated menstruation from those who did not; the mean leptin level of all 17 patients was lower than in healthy controls.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…Many investigations indicated a dysfunction of hypothalamus and metabolic changes in patients with anorexia nervosa (AN) associated with excessive weight loss. Most AN patients have low level of estradiol and show amenorrhea or irregular menstruation (10)(11)(12)(13)(14). A recent study indicated that AN patients have decreased REE ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study suggested the possibility that low BMI subjects with normal menstrual cycles do not have any differences in specific metabolic rates of different tissue organs compared to those with normal BMI. Women with low BMI, especially AN patients, have extremely low BW, FM, and BMD, dysfunction of the hypothalamus, metabolic differences, and irregular menstruation, such as amenorrhea (11)(12)(13)(14). However, only a few studies have investigated the differences in biochemical parameters and energy metabolism between young healthy women with low and normal BMI (19).…”
Section: Discussionmentioning
confidence: 99%